Study the Mechanism’s Glitches with Age for Neutron Stars - Abdullah, Sundus A.; Yaseen , Marwa M. (Iraqi Journal of Science, 2021)
Glitches are sudden increases in the rotational frequency (ν) of a neutron star.Glitches usually occur as fractional increase in the frequency of the order of ⁄= - .In this work we study the glitch in normal and magnetar pulsar stars,glitches are small or absent in the millisecond pulsar star because it is old starwhereas the weak glitch activity of young pulsars by the fact that their internaltemperatures are still too high for the crust to store a large stress .The results showedthat NART (pulsed emission only at infrared) normal pulsar has more glitches thanAXP (Anomalous X-ray Pulsar) and HE (Spin-powered pulsar with pulsed emissionfrom radio to infrared or higher frequencies) stars, as the same time HE stars havemore glitches than AXP, in a good agreement with the previous studies. From theresults can be conclude that study of neutron star glitches is a very important studyin the evolution of neutron star as it helps in probing the neutron star interior.